Recapitulation of metabolic defects in a model of propionic acidemia using patient-derived primary hepatocytes - Chapman, Kimberly A.; Collado, Maria S.; Figler, Robert A.; Hoang, Stephen A.; Armstrong, Allison J.; Cui, Wanxing; Purdy, Michael; Simmers, Michael B.; Yazigi, Nada A.; Summar, Marshall L.; Wamhoff, Brian R.; Dash, Ajit (Molecular genetics and metabolism, 2016)
Propionic acidemia (PA) is a disorder of intermediary metabolism with defects in the alpha or beta subunits of propionyl CoA carboxylase (PCCA and PCCB respectively) enzyme. We previously described a liver culture system that uses liver-derived hemodynamic blood flow and transport parameters to restore and maintain primary human hepatocyte biology and metabolism utilizing physiologically relevant milieu concentrations. In this study, primary hepatocytes isolated from the explanted liver of an 8-year-old PA patient were cultured in the liver system for 10days and evaluated for retention of differentiated polarized morphology. The expression of PCCA and PCCB was assessed at a gene and protein level relative to healthy donor controls. Ammonia and urea levels were measured in the presence and absence of amino acid supplements to assess the metabolic consequences of branched-chain amino acid metabolism in this disease. Primary hepatocytes from the PA patient maintained a differentiated polarized morphology (peripheral actin staining) over 10days of culture in the system. We noted lower levels of PCCA and PCCB relative to normal healthy controls at the mRNA and protein level. Supplementation of branched-chain amino acids, isoleucine (5mM) and valine (5mM) in the medium, resulted in increased ammonia and decreased urea in the PA patient hepatocyte system, but no such response was seen in healthy hepatocytes or patient-derived fibroblasts. We demonstrate for the first time the successful culture of PA patient-derived primary hepatocytes in a differentiated state, that stably retain the PCCA and PCCB enzyme defects at a gene and protein level. Phenotypic response of the system to an increased load of branched-chain amino acids, not possible with fibroblasts, underscores the utility of this system in the better understanding of the molecular pathophysiology of PA and examining the effectiveness of potential therapeutic agents in the most relevant tissue. •We describe an organotypic liver model for propionic acidemia using patient derived hepatocytes.•Hepatocytes in model retained differentiated morphology and function stably over 10days.•Molecular enzymatic defect was stably retained at gene and protein level.•Increased ammonia production by patient derived hepatocytes in response to amino acid loading in model•Similar responses not exhibited by healthy donor hepatocytes in model